2007
DOI: 10.1038/nn1984
|View full text |Cite
|
Sign up to set email alerts
|

Control of planar divisions by the G-protein regulator LGN maintains progenitors in the chick neuroepithelium

Abstract: The spatio-temporal regulation of symmetrical as opposed to asymmetric cell divisions directs the fate and location of cells in the developing CNS. In invertebrates, G-protein regulators control spindle orientation in asymmetric divisions, which generate progeny with different identities. We investigated the role of the G-protein regulator LGN (also called Gpsm2) in spindle orientation and cell-fate determination in the spinal cord neuroepithelium of the developing chick embryo. We show that LGN is located at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
239
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(261 citation statements)
references
References 50 publications
17
239
3
Order By: Relevance
“…In both the spinal cord and cerebral cortex, as in the majority of DT divisions, LGN localizes to lateral domains, where LGN loss increases oblique/perpendicular divisions, suggesting that LGN normally promotes planar divisions (Morin et al, 2007;Konno et al, 2008;Peyre et al, 2011;Shitamukai et al, 2011). However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In both the spinal cord and cerebral cortex, as in the majority of DT divisions, LGN localizes to lateral domains, where LGN loss increases oblique/perpendicular divisions, suggesting that LGN normally promotes planar divisions (Morin et al, 2007;Konno et al, 2008;Peyre et al, 2011;Shitamukai et al, 2011). However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, during asymmetric cell division, Par-3 recruits proteins such as Inscuteable, which in turn recruits Partner of Inscuteable (Pins) (Cai et al, 2003;Siller et al, 2006). Pins directly associates with heterotrimeric G-protein subunits and microtubuleassociated proteins to dictate the orientation of the microtubules and their positioning along the cell cortex (Izumi et al, 2006;Siller et al, 2006;Morin et al, 2007;Konno et al, 2008). Could redundant mechanisms exist in the SC, whereby Par-3 recruits microtubule-associated proteins to position and orient microtubules so that polymerization may lead to elongation, membrane spreading, and/or proper positioning of the SC as ensheathment initiates?…”
Section: Discussionmentioning
confidence: 99%
“…Ags3-null mice show no defects in brain morphology or function (Blumer et al, 2008). By contrast, knocking out Lgn randomizes the orientation of normally planar neuroepithelial divisions, consistent with it having a role in mitotic spindle orientation in the developing brain (Morin et al, 2007;Konno et al, 2008). The mammalian Mud homolog NuMA (a nuclear protein that associates with the mitotic apparatus; Numa1 -Mouse Genome Informatics) has a role in the establishment and maintenance of spindle poles (Sun and Schatten, 2006;Silk et al, 2009).…”
Section: Parallels To Mammalian Neural Stem Cellsmentioning
confidence: 92%